ESTIMATING THE UNDERESTIMATION PROFILE OF HEALTH SERVICE NEEDS THROUGH TELEPHONE COUNSELING CENTERS - Guimarães Junior, Djalma Silva; Melo, Fagner José Coutinho de; Santâ€™anna, Carlos Henrique Michels de; Soares, Eduardo José Oenning; Ferraz Júnior, Gileno; Medeiros, Denise Dumke de (Revista de Negócios, 2020)
The public and private health systems around the world face an expansion of services in parallel with the demand for improved quality and cost savings. Quality and efficiency of such systems are affected by the underestimation of the needs for patient care, compromising the clinical condition of the patient and system costs. The objective of this study is to identify the factors that determine the underestimation of the need for health services in Brazil. The survey used data collected from medical advice call center reports, totaling 19.690 observations; 2.166 of these have involved underestimation of needs, wherein the complexity of the intention of the patient is smaller than the recommendation proposed by the physician, which is divided into very or less critical. Through a logistic regression model, it was possible to estimate the critical factors in determining the underestimation in very and less critical needs for health services in Brazil. The closeness to the weekend increases the probability of a very critical underestimation. Daytime hours feature a very critical underestimation tendency. In terms of age groups, we can see a probability of very critical underestimation in younger individuals. This study showed that the user profile that was most likely to have very critical underestimation of the demand for health care was that of the underage individual who calls on weekends and in the early hours of the day.